THE APPLICATION OF THE EUROPEAN PRINCIPLES FOR GOOD ADMINISTRATION IN THE REPUBLIC OF MACEDONIA DE LEGE LATA AND DE LEGE FERENDA - Davitkovski Borche, Pavlovska-Daneva Ana, Ivana Shumanovska-Spasovska, Elena Davitkovska (Varazdin Development and Entrepreneurship Agency, Varazdin, Croatia / Faculty of Law University of Split, Croatia / University of Split, Croatia / University Department for Forensic Sciences, Croatia / Faculty of Law University of Mostar, Bosnia and Herzegovina / Faculty of Management University of Warsaw, Poland / University North, Croatia / Faculty of Law, Economics and Social Sciences Sale - Mohammed V University in Rabat, Morocco, 2018)
It is common knowledge that the organization, the functioning and the modeling of the administrative systems is a national question for every state, which leaves the European Union without a direct influence in the respective area. On the other hand, there is no doubt that by constantly emphasizing the public administration reforms as a key factor for integration, the Union becomes more and more relevant in that respect. Hence, the European institutions and organizations - especially the European Council - play a major role in the establishing of the fundamental European public administration principles. SIGMA is an organization also responsible for control over the fulfillment of the European public administration principles and gives directions on how to achieve these principles. As a part of numerous international acts, declarations and resolutions, these principles’ aim is to harmonize the member states’ governance systems in light of the way administrative bodies enforce their competences covering also the quality of services and the overall relationship between the authorities and the citizens. This way, certain European standards which, among other things, have a mandatory character are set. All the states striving to join the European Union have to undertake all the measures that will ensure a consistent application of the principles of the European administrative space and the acquis communitaire. Consequently, as one of the states claiming to join the Union, the Republic of Macedonia is also obliged to acquire such administrative capacities that will guarantee the application of the acquis communautaire - the general Administrative Law principles. This research is therefore focused on the importance of the European principles when speaking about the public administration quality, efficiency, effectiveness, transparency and responsibility. It analyses the legal framework where the European principles are set out, as well as the mechanisms the authorities and bodies undertake in order to ensure better execution of their responsibilities (e.g. electronic communication, enhanced inter-institutional cooperation and communication, training for officials and servants, etc.). 31st International Scientific Conference on Economic and Social Development – “Legal Challenges of Modern World” – Split, 7-8 June 2018 55 Thus, by examining the applicable legislation which regulates the public administration organization and operation we will try to identify and outline the key measures to be taken by the policy makers as to ensure not just de jure but also de facto strengthening of the public sector. In other words, we are referring to the steps necessary to improve the quality of public services and to modernize the administrative procedure, while still achieving depolitization and higher ethical standards. This is in fact the basic objective of the Public Administration Reform Strategy which is based on the progress Reports the European Commission delivers regularly (annually) delivers to the Republic of Macedonia. Keywords: acquis communautaire. European integration, public administration, principle of efficiency and effectiveness
Keywords: acquis communautaire. European integration, public administration, principle of efficiency and effectiveness